2023
DOI: 10.3390/agronomy13071941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Ratios of Red and Blue Light on Maximum Stomatal Conductance and Response Rate of Cucumber Seedling Leaves

Abstract: Light can regulate leaf stomatal development and movement, but the effects of different red-to-blue light mass ratios on leaf stomatal morphology and openness are not fully understood. In this trial, five different red-to-blue light (R:B) ratio treatments were used to study the changes in morphology, photosynthesis, and stomatal-related indexes of cucumber seedlings under fixed light intensity (200 μmol·m−2·s−1). The results showed that the thickness of spongy tissue and stomatal size (SZ) of cucumber seedling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
1
5
0
Order By: Relevance
“…Interestingly, Melaleuca cultivated in vitro under blue LED light presented the lowest density of stomata, regardless of the presence of BAP. The opposite was observed in Cucumber seedlings, in which the relative reduction in red light and the increase in blue light resulted in the highest stomatal density (Li et al 2023). Izzo et al (2021) reported reduced stomatal density both under red or blue monochromatic light, while their combination (red + blue light) increased stomatal density.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, Melaleuca cultivated in vitro under blue LED light presented the lowest density of stomata, regardless of the presence of BAP. The opposite was observed in Cucumber seedlings, in which the relative reduction in red light and the increase in blue light resulted in the highest stomatal density (Li et al 2023). Izzo et al (2021) reported reduced stomatal density both under red or blue monochromatic light, while their combination (red + blue light) increased stomatal density.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, in our previous research [3], we documented that both long-term R-and B-light treatment increased NPQ amplitude, while G and RGB light lowered its value due to the reduced accumulation of NPQ-related proteins. At the same time, previous research [12,[21][22][23][24] has shown that the quality of growth light influences gas exchange, especially due to the modification of stomatal development and movement. The main conclusions from these studies are that B light stimulates stomata opening more than R light, while the addition of G light to the spectrum reduces stomatal conductance via both contractions of stomata dimension and density, as well as reduced stomatal openness.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, a strong positive correlation was reported between NIR reflectance and stomatal conductance [31]. Moreover, the increase in stomatal conductance can promote the enhancement of photosynthesis [32][33][34]. Therefore, the changes in tea seedlings' leaf structure in the STS pattern are worthy of further study.…”
Section: Soybean-tea Intercropping Changed the Spectral Characteristi...mentioning
confidence: 97%